HUBUNGAN ANTARA KEBERSYUKURAN (GRATITUDE) DENGAN STRES PADA IBU YANG MEMILIKI ANAK DENGAN GANGGUAN SPEKTRUM AUTISME - Rosa Andriani; Agnes Maria Sumargi (Universitas Katolik Widya Mandala Surabaya, 2019)
In comparison to typical developing children, children with autism spectrum disorder have unusual development. Nurturing and raising children with special needs, particularly children with autism spectrum disorder, are challenging. Parents often experience distress because have to support and accompany their children in a wide range of therapies that can be tiring and costly. Positive emotions such as gratitude could be developed to alleviate parental stress. This study aimed to test the relationship between gratitude and stress among mothers who had children with autism spectrum disorder. Participants were 40 mothers of children with autism spectrum disorder. They were recruited from therapy centres, special schools, and inclusive schools in Sidoarjo. The measures used in the study were the Depression Anxiety Stress Scale (DASS-21) and Gratitude Questionnaire-6 (GQ-6). Results showed a significant, negative correlation between gratitude and maternal stress, r = -0.310, p = 0.007 (p < 0.05). The higher the levels of maternal gratitude, the lower the levels of maternal stress, and vice versa, the lower the levels of maternal gratitude, the higher the levels of maternal stress. The tendency to be grateful seems to reduce the stress levels of mothers who had children with autism spectrum disorder.